Ocular regenerative medicine using decellularized tissues - Chandrasekharan, Ajeesh; Yazdani, Erfan; Mahdian, Aida; Shahidi Marnani, Seyed AmirAbbas; Askari, Shadi (Journal of Composites and Compounds, 2022)
Decellularization is the process of eliminating the cellular compartment of living tissues chemically or physically, resulting in an acellular extracellular matrix (ECM) scaffold that can be employed for a variety of reasons. Decellularized matrices are useful for tissue engineering applications because they preserve the tissue-specific mechanical, biochemical, and structural microenvironments while facilitating cellular engraftment and activities in the matrix. A variety of tissues have been decellularized by a variety of mechanical, chemical, and enzyme-based techniques and used to create bio scaffolds for diverse cell types such as primary cells, progenitor cells, and stem cells. Various applications and approaches are used in ocular tissue engineering and regeneration. Repairing the damaged structure in the corneal epithelium or the retinal ganglion cells is one of them. Scaffolds of biocompatible, biodegradable, natural, or synthetic polymers may be used in such applications. Stem cells can also be used to replicate vital cells in order to maintain vision function. Decellularized matrices can be used to create scaffolds for ocular tissue engineering, artificial arteries, cell culture matrices, and transplantation carriers, among other things. To gain a better understanding of regenerative medicine, we'll look at different types of decellularized tissue matrices and how they've been used to create artificial organs and regenerate injured tissues.